Literasi Kewirausahaan Dalam Penguatan Karakter Siswa di SMA Islam Nabilah, Batam, Kepulauan Riau - Sarmini Sarmini; Diana Titik Windayati; John Friadi (I-Com: Indonesian Community Journal, 2024)
ABSTRACT Entrepreneurial literacy refers to an individual’s comprehension of entrepreneurs and their positive, creative and innovative traits in transforming business ideas into opportunities that benefit themselves and the community or consumers. Referring to BPS data, the open unemployment rate for high school graduates and the equivalent is still quite high in the Riau Islands, especially Batam City, 7.85%. The aim of this activity is to enhance the understanding of the younger generation, especially Nabilah Islamic High School students, about entrepreneurship. The material was delivered by providing an understanding of entrepreneurship, then continued with discussions, website introductions and website management simulations. Training activities help improve students' comprehension of entrepreneurship which can create their own jobs. The aim of this activity is to increase the understanding of the younger generation, especially Nabilah Islamic High School students, about entrepreneurship. The material was delivered by providing an understanding of entrepreneurship, then continued with discussions, website introductions and website management simulations. Training activities provide benefits in increasing students' understanding of entrepreneurship which can generate their own employment opportunities. Entrepreneurial literacy activities carried out at Nabilah Islamic High School, Batam City include socialization, creating entrepreneurial websites for students and training in managing entrepreneurial websites as well as holding market days in order to instill an entrepreneurial spirit. Keywords: Keyword 1; Entrepreneurial Literacy, Keyword 2; Website